2019
DOI: 10.1101/527630
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Unsupervised Machine Learning for Analysis of Coexisting Lipid Phases and Domain Growth in Biological Membranes

Abstract: 2 Phase separation in mixed lipid systems has been extensively studied both experimentally and 3 theoretically because of its biological importance. A detailed description of such complex systems 4 undoubtedly requires novel mathematical frameworks that are capable to decompose and 5 categorize the evolution of thousands if not millions of lipids involved in the phenomenon. The 6 interpretation and analysis of Molecular Dynamics (MD) simulations representing temporal and 7 spatial changes in such systems is st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 71 publications
(66 reference statements)
0
1
0
Order By: Relevance
“…Therefore, when making a diagnosis, it will be possible to provide suggestions for improving the system. Previous studies demonstrated that lipid bilayer membranes (Walter et al, 2020) and lipid mixtures (Löpez et al, 2019) contribute to understanding how phase separation occurred using machine learning systems. These aforementioned studies, along with the present research, aim to understand phase separation on lipid membranes using machining learning systems.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, when making a diagnosis, it will be possible to provide suggestions for improving the system. Previous studies demonstrated that lipid bilayer membranes (Walter et al, 2020) and lipid mixtures (Löpez et al, 2019) contribute to understanding how phase separation occurred using machine learning systems. These aforementioned studies, along with the present research, aim to understand phase separation on lipid membranes using machining learning systems.…”
Section: Resultsmentioning
confidence: 99%